Pengaruh Penerapan Prinsip-Prinsip Good Corporate Governance dan Budaya Tri Hita Karana pada Kinerja Keuangan - Bali Sakhya Prawira, I Gusti Ngurah Gede; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p15, 2020)
The purpose of this study was to examine the effect of the principles of good corporate governance and the tri hita karana culture on financial performance. The study was conducted in all savings and loan cooperatives in Tabanan district. The respondents in this study were the chairman, secretary, and treasurer of the cooperative. The population in this study amounted to 86 cooperatives. The samples in this study were 71 cooperatives obtained by the proportionate stratified random sampling method. Data collection was carried out by distributing questionnaires and the analysis technique used multiple linear regression analysis. The results showed that the principles of good corporate governance and tri hita karana culture had a positive effect on financial performance. This means that the better the application of the principles of Good Corporate Governance and the culture of tri hita karana in Savings and Loan Cooperatives in Tabanan Regency, it will tend to improve the financial performance of these cooperatives. Keywords: Financial Performance; Principles of Good Corporate Governance; Tri Hita Karana Culture.